ACID-BASE PROPERTIES OF MONTMORILLONITE AND INTERACTIONS WITH ENZYMES THROUGH REM INVESTIGATIONS (Sciences & Technology. A, exactes sciences, 2004)
Interactions of montmorillonite-rich clay materials with enzymes were investigated. A 2:1 layer typeraw clay mineral was purified, then ion-exchanged with Na+, K+ (Na-Mt and K-Mt), Ca2+ and Mg2+ (Ca-Mt and Mg-Mt), and further contacted with various enzyme suspensions containing α-amylase, β-amylase, cellulase, invertase, lipase, peroxidase, pectinase, urease, protease or tripsine. The acid andbase properties were measured via thermal programmed desorption of NH3 and CO2, respectively. It wasfound that Ca-Mt and Mg-Mt exert stronger interactions with enzymes, generating coarser flake-shapedclay particles, as compared to Na-Mt and K-Mt. This specific behaviour is explained in terms of clayaffinity towards enzymes, and correlated to the clay acid-base properties, that could have a great interestfor soil chemistry. The shape and the size of clay particles were also discussed through reflectionelectron microscopy.